An approach for assessing whether agricultural projects help smallholders transition to better livelihood strategies: A Malawian case study - Timu, Anne G.; Hazell, Peter B. R.; Savastano, Sara (Elsevier, 2024)
Agricultural projects typically aim to promote the uptake of project components amongst targeted small farm populations to improve their farm productivity and welfare. While this approach can be an important first step towards improving smallholder livelihoods, it ignores alternative and often superior livelihood options that might arise within the rural transformation process, particularly in commercial agriculture and the rural nonfarm economy. We argue that the design of smallholder projects implemented within regions already undergoing a dynamic transformation and/or projects which have significant value chain components, should be broadened to assist smallholders in making successful transitions to their best livelihood options. For such projects, monitoring and evaluation activities should track livelihood transitions as well as the usual assessments of productivity and welfare outcomes. To help operationalize such an approach, we propose a typology of smallholder livelihood strategies that can track transitions over time and illustrate its use with data from the Sustainable Agricultural Production Program (SAPP), an agricultural value chain project in Malawi. Using available household panel data and quasi-experimental econometric approaches, we find that the project helped smallholders transition out of subsistence farming to market-oriented farming and helped already existing market-oriented farmers remain as such. Even though the project did not have any specific components designed to promote off-farm incomes, nevertheless, it facilitated many farm household transitions to off-farm diversified livelihoods, possibly due to spillover benefits generated within the local nonfarm economy. All SAPP facilitated transitions led to increases in household incomes. We conclude with some lessons for designing, monitoring, and the evaluation of future agricultural projects.